2022
DOI: 10.4236/ajps.2022.139088
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profile and Antioxidant, Anti-Inflammatory Activity of <i>Annona senegalensis, Ipomoea batatas, Terminalia superba</i> and <i>Psidium guajava</i> Linn Extracts Used in Benin

Abstract: The purpose of this study is to quantify the polyphenolic content and evaluated anti-inflammatory and antioxidant activity of four plants extracts of Annona senegalensis, Ipomoea batatas, Terminalia superba and Psidium guajava. Phenolic and flavonoid contents were determined by Folin-Ciocalteu and aluminum trichloride methods, respectively with ethanolic extract. The antioxidant activity was accessed by DPPH and FRAP methods. The results of the analysis of this study indicate that the ethanol extracts of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…In the research of Chintha et al [42], purple-fleshed sweet potato was found to possess the highest total phenolic content with 2.1 and 2.84 mg GAE/100 g FW found, respectively, in ethanol and aqueous extracts. Namely, total phenols in the amount of 179.8 mg GA/100 g in a dried orange sample obtained using the same solvent mixture was obtained by Šeregelj et al [16], while similar research [43] indicated 266.39 mg GA/100 g of total phenolics in an ethanol solution of I. batatas.…”
Section: Bioactive Compounds and Biological Potentials Of Sweet Potat...supporting
confidence: 63%
See 1 more Smart Citation
“…In the research of Chintha et al [42], purple-fleshed sweet potato was found to possess the highest total phenolic content with 2.1 and 2.84 mg GAE/100 g FW found, respectively, in ethanol and aqueous extracts. Namely, total phenols in the amount of 179.8 mg GA/100 g in a dried orange sample obtained using the same solvent mixture was obtained by Šeregelj et al [16], while similar research [43] indicated 266.39 mg GA/100 g of total phenolics in an ethanol solution of I. batatas.…”
Section: Bioactive Compounds and Biological Potentials Of Sweet Potat...supporting
confidence: 63%
“…Based on the data presented in Table 4 , the convective drying technique seems to be the method of choice for maintaining and determining the pharmaceutical activities of sweet potato samples. Depending on the type of extracts and batatas cultivators, α-amylase enzyme inhibitory activity varied from 56.85 to 98.78% in the research of Chintha et al [ 43 ]. AHgA natural property of sweet potatoes is considered to be based on their phytochemical content, correlated to the presence of flavones.…”
Section: Resultsmentioning
confidence: 99%